On the relative performance of multi-strategy and funds of hedge funds - Vikas Agarwal; Jayant R. Kale (University of Cologne, Centre for Financial Research (CFR), 2007)
Recently, there has been explosive growth in two products from the hedge fund industry - multi-strategy (MS) funds and funds of hedge funds (FOFs), both of which offer diversification across different hedge fund strategies. In well-functioning markets, both investment vehicles should offer similar returns. Over the period 1994 - 2004, we find that MS funds outperform FOFs on a risk-adjusted basis by 2.6% to 4.8% per year on gross-of-fee and by 3.0% to 3.6% per year on net-of-fee basis. The superior performance of MS funds continues to hold even when we control for fund characteristics such as size, management and incentive fees, and other conventional control variables. Since FOFs underperform MS funds on both netand gross-of-fee basis, their underperformance cannot be entirely explained by their double-layered fee structure. The question then is how MS funds and FOFs can co-exist in equilibrium in view of the significant differential in performance? We suggest that investors perceive greater agency risk in the structure of MS funds relative to FOFs and therefore require greater compensation for investing in MS funds. MS funds are able to generate these higher returns because they possess greater investment flexibility and are able to invest in less liquid assets. It is also possible that MS funds generate greater returns because managers with better ability self-select into joining MS funds and the competition among MS funds results in the rents from superior ability being passed on to the investors in the form of better returns. Controlling for the differences in agency risk, flexibility, and fee structure between MS funds and FOFs, our results suggest that self-selection by managers with superior ability in MS funds may be the driving force behind their superior performance relative to FOFs.
Keywords: G11; G12; 330; Multistrategy hedge funds; funds of hedge funds; performance; fees; agency risk; investment flexibility